Post-Operative Benefits of Animal-Assisted Therapy in Pediatric Surgery: A Randomised Study - Calcaterra, Valeria (PLoS One, 2015)
BACKGROUND: Interest in animal-assisted therapy has been fuelled by studies supporting the many health benefits. The purpose of this study was to better understand the impact of an animal-assisted therapy program on children response to stress and pain in the immediate post-surgical period. PATIENTS AND METHODS: Forty children (3–17 years) were enrolled in the randomised open-label, controlled, pilot study. Patients were randomly assigned to the animal-assisted therapy-group (n = 20, who underwent a 20 min session with an animal-assisted therapy dog, after surgery) or the standard-group (n = 20, standard postoperative care). The study variables were determined in each patient, independently of the assigned group, by a researcher unblinded to the patient’s group. The outcomes of the study were to define the neurological, cardiovascular and endocrinological impact of animal-assisted therapy in response to stress and pain. Electroencephalogram activity, heart rate, blood pressure, oxygen saturation, cerebral prefrontal oxygenation, salivary cortisol levels and the faces pain scale were considered as outcome measures. RESULTS: After entrance of the dog faster electroencephalogram diffuse beta-activity (> 14 Hz) was reported in all children of the animal-assisted therapy group; in the standard-group no beta-activity was recorded (100% vs 0%, p<0.001). During observation, some differences in the time profile between groups were observed for heart rate (test for interaction p = 0.018), oxygen saturation (test for interaction p = 0.06) and cerebral oxygenation (test for interaction p = 0.09). Systolic and diastolic blood pressure were influenced by animal-assisted therapy, though a higher variability in diastolic pressure was observed. Salivary cortisol levels did not show different behaviours over time between groups (p=0.70). Lower pain perception was noted in the animal-assisted group in comparison with the standard-group (p = 0.01). CONCLUSION: Animal-assisted therapy facilitated rapid recovery in vigilance and activity after anaesthesia, modified pain perception and induced emotional prefrontal responses. An adaptative cardiovascular response was also present. TRIAL REGISTRATION: ClinicalTrials.gov NCT02284100